“Sad Kertih”: Sastra Agama, Filosofi, dan Aktualisasinya - Wiana, I Ketut (Badan Riset dan Inovasi Daerah Provinsi Bali, 2018)
Sad Kerti is six kertis or kertihs (noble behavior) which consists of atma, samudra, wana, danu, jagat, and jana. It is a Hindu concept that is very basic and meaningful and challenging to realize in reality. The six are the basis of this life. Realizing this, the government of Bali, through the new Governor and the new Deputy Governor, has built a comprehensive plan through the paradigm of